EFEKTIVITAS PELATIHAN SELF COMPASSION UNTUK MENGHILANGKAN PROKRASTINASI AKADEMIK SISWA KELAS XI SMA NEGERI 10 PONTIANAK - Shaina Amanda, Gusti Ayu; Asrori, Muhammad; Yuline, Yuline (Universitas Tanjungpura, 2023)
This study aimed at finding out the effect of self-compassion exercises to overcome academic procrastination given to all the second year student at SMA Negeri 10 Pontianak, which was 159 students. The method used in this study was a Pre-Experimental Design that consisted of One-Group Pretest-Posttest Design. The selection of samples used was non-probability with purposive sampling method, the sample used in this study was 14 students with high level of procrastination. The findings in this study indicated the mean of pre-test was 97,00 and the mean of post-test was 59,71. The result of Paired Sample T-Test was 8,487 with Sig. (2 tailed)0,00 0,05, where Ha was accepted and H0 was rejected. Accordingly, there was a significant difference between before and after self-compassion exercises. The researcher concluded that self-compassion exercises was effectively overcome academic procrastination for second year students at SMA Negeri 10 Pontianak